Incentives for agroecological transition in Ucayali, Peru: Resilient and inclusive systems - Blanco Garcia, Maria Alejandra; Araujo De Lima, Silvia; Mosquera Escobar, Leslie Estefany; Ivanova, Yovita; Sanchez Choy Sanchez, Jose Gerardo; Varon Molina, Adriana Patricia; Marulanda Duran, Luis Alejandro; Mockshell, Jonathan (2025)
The Peruvian Amazon, one of the most biodiverse regions in the world, faces numerous interconnected challenges, including biodiversity loss and soil degradation. The Private Sector Incentives and Investments (PSii) project—implemented by the Alliance of Bioversity International and CIAT, funded by the European Commission, and managed by the International Fund for Agricultural Development (IFAD)—marks a significant step toward fostering sustainable and inclusive food systems. It operates under the CGIAR’s Agroecological Transitions Program for Building Resilient, Inclusive Agricultural and Food Systems (TRANSITIONS).